The roles of competencies in the new venture creation among e-Commerce entrepreneurs in Malaysia - Ahmad Firdause Md Fadzil; Mohd Rafi Yaacob; Mohd Nazri Muhayiddin (2017)
Over the past three decades, studies on entrepreneurs; the main components behind entrepreneurship particularly for new venture creation processes, have been widely highlighted by researchers. An entrepreneur is regarded as the main actor in entrepreneurship as he/she is the one who is responsible for a new venture creation. It involves a lot of thinking and decision making in the establishment of a new enterprise. Most past studies focused more on the psychological aspects of entrepreneurs, looking at the process of creating new ventures, but less on entrepreneurial competencies which lead to new venture creations. In order to fill the lacunae, the aim of this study is to identify the role of entrepreneurial competencies that contribute to the creation of new e-commerce businesses in Malaysia. This research used a case studies approach in which data were collected by face to face interviews - a total of twelve e-commerce entrepreneurs throughout the country from May 2013 to December 2014. The findings of this study have found that the entrepreneurial competencies in both computer and communication skills have largely contributed to the creation of new businesses. These skills are really essential as it facilitates entrepreneurs in expediting their creation of new ventures. To encourage entrepreneurial activities in the country, it is highly important for the government to emphasise on the elements of entrepreneurial competencies among the people. This is a crucial step as it not only benefits the society as a whole, but also the future of the country